2017
DOI: 10.1016/j.fertnstert.2017.02.120
|View full text |Cite
|
Sign up to set email alerts
|

A first-choice combined oral contraceptive influences general well-being in healthy women: a double-blind, randomized, placebo-controlled trial

Abstract: This study demonstrates a statistically significant reduction in general well-being by a first-choice OC in comparison with placebo in healthy women. We found no statistically significant effects on depressive symptoms. A reduction in general well-being should be of clinical importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(77 citation statements)
references
References 32 publications
4
71
2
Order By: Relevance
“…In a recent paper based on the same clinical trial as here, we found evidence of negative effects of this OC on general well-being (Zethraeus et al 2017), and on sexual well-being for some of our secondary outcome measures but not our primary outcome measure (Zethraeus et al 2016). Thus, even though this OC does not appear to affect economic preferences, there is evidence of other effects of this OC using the same setup as here.…”
Section: Discussionsupporting
confidence: 60%
“…In a recent paper based on the same clinical trial as here, we found evidence of negative effects of this OC on general well-being (Zethraeus et al 2017), and on sexual well-being for some of our secondary outcome measures but not our primary outcome measure (Zethraeus et al 2016). Thus, even though this OC does not appear to affect economic preferences, there is evidence of other effects of this OC using the same setup as here.…”
Section: Discussionsupporting
confidence: 60%
“…One RCT among women who were sterilised or whose partners were sterilised taking a COC, POP or placebo found no difference in depressive symptoms by the third month of treatment 324. A recent large, double-blind RCT325 randomised 340 women in Sweden to a standard 30 μg EE/LNG COC or placebo taken for 21 days with a 7-day pill-free interval for three cycles.…”
Section: Side Effects Associated With Chc Usementioning
confidence: 99%
“…It seems necessary, therefore, to determine as to whether it is ethically and medically correct to call a device safe if it has the potential of affecting adversely a woman's health. As the term "safe" is used nonchalantly in some instances, it must be suggested that future research investigate not only singular adverse events in the use of contraceptive methods but integrate these events into the larger context of quality of life [13]. For this purpose, a common terminology criteria for adverse events could be formulated following the instruments developed by the National Cancer Institue [14].…”
Section: Resultsmentioning
confidence: 99%
“…This ranking shows "tubal sterilization" (Pearl index 0.09-0.4) together with "depot-gestagens" (Pearl index 0.03-0.9), as the most efficacious, followed by "monophasic combined pill" (0.1-1.0), "oral hormonal sequential contraceptives" (0.2-1.4), "minipill" (1), "intrauterine pessary" (0.14-2) and the symptothermal method (0.8) [4]. Concerning the other natural family planning methods, "basal temperature" (Pearl index of 1-3) seems comparable to "diaphragm and spermicide" (Pearl index 2-4) or "condom" (4-5), while "cervical mucus" (15-32) and "calendar" (15-40) roughly approximate the efficacy of "chemical spermicides" (12)(13)(14)(15)(16)(17)(18)(19)(20) …”
Section: Tables Surveys and Ratings Of Contraceptive Methodsmentioning
confidence: 99%